1991
DOI: 10.1203/00006450-199111000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Lung Volume, Gas Mixing, and Mechanics of Breathing in Mechanically Ventilated Very Low Birth Weight Infants with Idiopathic Respiratory Distress Syndrome

Abstract: ABSTRACT. We assessed pulmonary function in 14 mechanically ventilated newborn very low birth weight infants with idiopathic respiratory distress syndrome by means of a face-out, volume displacement body plethysmograph and nitrogen washout analyses. Specially designed computer programs were used for calculations of lung volumes, ventilation, gas mixing efficiency, and mechanical parameters. In addition to very low compliance and moderately elevated resistance of the respiratory system, there were considerably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The presence of right-to-left shunting of blood in association with neonatal RDS is well documented (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Several investigators have suggested that the right-to-left shunting in infants with RDS occurs predominantly within the lungs (29,46,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of right-to-left shunting of blood in association with neonatal RDS is well documented (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Several investigators have suggested that the right-to-left shunting in infants with RDS occurs predominantly within the lungs (29,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that large right-to-left shunts predict an early death of infants with RDS. RDS is also complicated by intrapulmonary shunting of blood (28)(29)(30)(31)(32)(33)(34)(35). Regional atelectasis and hyaline membrane formations probably contribute greatly to the pathophysiology of the intrapulmonary shunting associated with RDS.…”
mentioning
confidence: 99%
“…We also showed, in a lung model, that FRC can be accurately assessed when the Fi02 in the breathing gas is as high as 0. 8. This was also the case in air breathing with a washout FiOz of only 0.…”
Section: Discussionmentioning
confidence: 87%
“…A nitrogen washout using an Fi02 of 1.0 was performed after ventilation ofthe model with an FiOz of 0. 8 compared with a series of washouts with Fi02 1.0 and a ventilatory Fi02 of 0.2 1. Ten washouts with each gas combination were performed.…”
Section: Methodsmentioning
confidence: 99%
“…69 Although a wide range of FRCs (from as low as a mean of 7.8 ml/kg to 15.5 ml/kg) was reported in ventilated infants with RDS using clinically determined PEEP ($4 cm H 2 O) and prior to surfactant administration, these values are significantly lower than those predicted from reference data generated in healthy infants breathing without assistance. 2,82,[91][92][93] The effect of varying PEEP level on FRC was assessed systematically. 24,69,70,74,94 Increasing PEEP consistently results in increases in FRC and oxygenation, 74,94 but the correlation between DPEEP and DFRC seems nonlinear.…”
Section: The Extent To Which Functional Findings Can Be Related To Pamentioning
confidence: 99%